In-Vitro Approaches to Predict and Study T-Cell Mediated Hypersensitivity to Drugs - Hammond, Sean; Thomson, Paul; Meng, Xiaoli; Naisbitt, Dean (Frontiers in Immunology, 2021)
Mitigating the risk of drug hypersensitivity reactions is an important facet of a given pharmaceutical, with poor performance in this area of safety often leading to warnings, restrictions and withdrawals. In the last 50 years, efforts to diagnose, manage, and circumvent these obscure, iatrogenic diseases have resulted in the development of assays at all stages of a drugs lifespan. Indeed, this begins with intelligent lead compound selection/design to minimise the existence of deleterious chemical reactivity through exclusion of ominous structural moieties. Preclinical studies then investigate how compounds interact with biological systems, where emphasis is placed on modelling immunological/toxicological liabilities. During clinical use competent, accurate diagnoses are sought to effectively manage patients with such ailments, and pharmacovigilance datasets can be used to stratify patient populations to optimise safety profiles. Herein, an overview of some of the in-vitro approaches to predict intrinsic immunogenicity of drugs and diagnose culprit drugs in allergic patients after exposure are detailed, and current perspectives and opportunities in areas are provided.